(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2021)
The Concentration Of Entreprises On One Market In A Single Country Does Not Guarantee Survival And Continuity Due To The Intensity Of Competition. It Is Also Difficult To Maintain The Market Share. Therefore, Entreprise Continues To Be Thinking About Internationalization And Trying To Exist In More Than One Market. More Than One Country. In View Of The Growing Interest In The Option Of Internationalization Of Algerian SME’s In Order To Build A Balanced Economy To Withstand Fluctuations In The Hydrocarbon Sector, And Because Institutions Find It Difficult To Enter The International Markets, Especially With Regard To Quality, Which Forces This Type Of Institutions To Pay Attention To Quality, Modern And Exclusive Quality To Ensure Its Accessibility To International Markets. This Study Is Intended To Determine The Extent To Which Algerian Smes Are Aware Of The Importance Of TQM In The Process Of Internationalization, In Order To Provide The Necessary Requirements For The Success Of The Process Of Internationalization Of Algerian Small And Medium Enterprises Within The Framework Of TQM. Keywords: Quality, Total Quality Management, Algerian SME’s, Internationalization, Strategy.